2021
DOI: 10.48550/arxiv.2108.08503
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Capacity Optimality of OAMP: Beyond IID Sensing Matrices and Gaussian Signaling

Abstract: This paper studies a large unitarily invariant system (LUIS) involving a unitarily invariant sensing matrix, an arbitrary signal distribution, and forward error control (FEC) coding. We develop a universal Gram-Schmidt orthogonalization for orthogonal approximate message passing (OAMP). Numerous area properties are established based on the state evolution and minimum mean squared error (MMSE) property of OAMP in an un-coded LUIS. As a byproduct, we provide an alternative derivation for the constrained capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…When CSI is only available at the receiver, the Gaussian capacity of MU-MIMO was obtained with Gaussian signaling [14]. However, for arbitrary input distributions, only the constrained capacity of P2P-MIMO was derived with independent and identically distributed (IID) channel matrices [15], [16] or unitarilyinvariant channel matrices [17], [18] by using the adaptive interpolation method and random matrix theory [15]- [17], or using the MMSE and decoupling properties of approximate message passing (AMP)-type algorithms [18], [19]. At present, it is unknown about the constrained capacity of MU-MIMO with arbitrary input distributions and unitarily-invariant channel matrices.…”
Section: A Information Theoretical Limit Of Mu-mimomentioning
confidence: 99%
See 4 more Smart Citations
“…When CSI is only available at the receiver, the Gaussian capacity of MU-MIMO was obtained with Gaussian signaling [14]. However, for arbitrary input distributions, only the constrained capacity of P2P-MIMO was derived with independent and identically distributed (IID) channel matrices [15], [16] or unitarilyinvariant channel matrices [17], [18] by using the adaptive interpolation method and random matrix theory [15]- [17], or using the MMSE and decoupling properties of approximate message passing (AMP)-type algorithms [18], [19]. At present, it is unknown about the constrained capacity of MU-MIMO with arbitrary input distributions and unitarily-invariant channel matrices.…”
Section: A Information Theoretical Limit Of Mu-mimomentioning
confidence: 99%
“…In [18], it provided the achievable rate analysis for OAMP in P2P coded linear systems with unitarily-invariant matrices and arbitrary signal distributions. In addition, the capacity optimality of OAMP was rigorously proven, where the achievable rate of OAMP achieves the system capacity under the constraints of channel matrices and input signals [18]. Furthermore, it was shown that OAMP outperforms AMP in physical random access channels [30] and the conventional Turbo receivers in P2P channels [18], [21].…”
Section: Challenges and Motivationmentioning
confidence: 99%
See 3 more Smart Citations